Counseling on the handling of tofu and tempe industrial waste in Bangkinang Kota District, Kampar Regency - Fatmayati Fatmayati; Sri Wahyuni; Hanifah Khairiah; Nur Asma Deli; Razita Hariani (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2023)
The development of the tofu and tempe industrial business in Bangkinang Kota District, Kampar Regency, is mainly carried out on a small and medium scale business, so in production and management, it experiences several limitations such as limited production equipment, production processes carried out traditionally, and limited knowledge in terms of management and treatment of waste. This community service activity aims to carry out activities to assist soybean grinding machine equipment and diesel motors in the Tofu-Tempe Industry Mrs. Helma and Mr. Ayusman to assist partners in the production process so that production activities can be carried out more effectively and economically with maximum results. In addition, this activity aims to provide information and training to the two partners on the handling and processing the resulting waste, which can be processed into organic liquid fertilizer. The results of this dedication show that the two tofu-tempe industry partners feel very useful with the activities that have been carried out because of the assistance of production equipment in the form of soybean milling machines and diesel motors as well as training on handling and processing the resulting waste into organic liquid fertilizer. It is hoped that this activity will create a positive synergy between tofu and tempe businesses and agricultural businesses around the tofu and tempe industry. Perkembangan usaha industri tahu dan tempe di Kecamatan Bangkinang Kota, Kabupaten Kampar banyak dilakukan dalam skala usaha kecil dan menengah sehingga dalam produksi dan pengelolaannya mengalami beberapa keterbatasan seperti keterbatasan peralatan produksi, proses produksi dikerjakan secara tradisional, serta keterbatasan pengetahuan dalam hal pengelolaan dan pengolahan terhadap limbah yang dihasilkan. Kegiatan pengabdian kepada masyarakat (PkM) ini bertujuan untuk melakukan kegiatan bantuan peralatan mesin giling kedelai dan motor diesel di Industri Tahu-Tempe Bu Helma dan Pak Ayusman untuk membantu mitra dalam proses produksi sehingga kegiatan produksi bisa dilaksanakan lebih efektif dan ekonomis dengan hasil yang maksimal. Selain itu, kegiatan ini bertujuan untuk memberikan informasi dan pelatihan kepada kedua mitra tentang penanganan dan pengolahan limbah yang dihasilkan yang dapat diproses menjadi pupuk cair organik. Hasil pengabdian ini menunjukkan kedua mitra industri tahu-tempe merasa sangat bermanfaat dengan kegiatan yang telah dilaksanakan karena adanya bantuan peralatan produksi berupa mesin giling kedelai dan motor diesel serta adanya pelatihan tentang penanganan dan pengolahan limbah yang dihasilkan menjadi pupuk cair organik. Kegiatan ini diharapkan munculnya suatu sinergi positif antara usaha tahu-tempe dengan usaha pertanian di sekitar industri tahu dan tempe.